(untitled) (Anclajes, 2018)
The fairy tale is key to analyzing Alejandra Pizarnik’s writing. Specifically, in the translation/rewriting of Valentine Penrose’s La comtesse sanglante (1962) to La Condesa sangrienta (1965), this genre is central because it works as an appropriation matrix. This matrix models Pizarnik’s version through revisiting a series of themes and elements specific to the genre, as well as a way to narrate, characterized by the presentation of vignettes or fragments of highly symbolic and visual density, and by a cut with the causality and linearity of a realistic tale. First, we will analyze the intertextualities between Pizarnik’s work and a corpus of two classical children’s stories: The Snow Queen (1845), by Hans Christian Andersen, and Snow White (1812) by the Brothers Grimm. Second, we will focus on the relation of Pizarnik’s work with its explicit hypotext, Valentine Penrose’s La comtesse sanglante, considering the aforementioned, that is, the way fairy tales operate as a matrix in this transfer.